Stability of the Demand for Real Narrow Money in lndonesia - Reza Anglingkusumo (Tinbergen Institute, 2005)
The stability of the demand for real Ml in Indonesia is empirically examinedusing quarterly data between 1981 and 2002. A cointegrated VAR methodology thatisolates the period of structural breaks in the data generating process of the variables,caused by the Asian crisis, is used. The results show that the nominal Ml demandfunction is long run homogenous in the price level and the price level itself isendogenous in the equation for nominal Ml. Therefore, a reparameterization towardsthe real Ml demand function is necessary. In the pre and post Asian crisis era, thedemand function for real Ml in Indonesia is empirically stable and consists of a smallnumber of variables. In the long run, the real private household consumption spendingforms the permanent part of the demand for real Ml balances. Meanwhile, in theshort run, the opportunity cost of holding real Ml balances, measured by the l-monthnominal interest rate of time deposits in commercial banks, and agents' seasonalpreference for real money balances, are key determinants of the demand for real Mlbalances. In addition, there is evidence of a co-breaking relationship between the realMl balances and the real private household consumption spending in Indonesiaduring the Asian crisis.
Keywords: E41; C12; 330; money demand; cointegrated V AR; structural breaks; co-breaking; Asian crisis; Indonesia; Geldnachfrage; Geldmenge; VAR-Modell; Kointegration; Strukturbruch; Indonesien; Asien; Finanzkrise